KAJIAN PERAN UPT PERPUSTAKAAN UNIVERSITAS SEBELAS MARET SURAKARTA DALAM PEMBERDAYAAN LITERASI MASYARAKAT DI SEKITAR KAMPUS SEBAGAI UPAYA MENDUKUNG TRI DHARMA PERGURUAN TINGGI - Agus Sriyono; Lilis Sulistyaningsih; Hardian Putri Nuryana Putri Nuryana (BIBLIOTIKA : Jurnal Kajian Perpustakaan dan Informasi, 2021)
Libraries have a role to foster and develop a literacy culture. The library is one of the information centers because it provides many books and knowledge needed as scientific references. The existence of the Sebelas Maret University (UNS) campus is inseparable from the surrounding community. So it is hoped that there will be a symbiotic mutualism (mutual benefit) between the academic community of the UNS campus, especially the UPT Library of UNS Surakarta and the surrounding community. This study aims to examine the role of UPT Sebelas Maret University (UNS) Surakarta Library in empowering the literacy of the community around the campus. Libraries have an important role as a center for knowledge resources, to support the process of education, research and community service, including the role of libraries to participate in developing the literacy of the community around campus. This research was conducted in June 2021 using quantitative and qualitative research methods with purposive sampling as the source of information. The sample population in this study were people directly adjacent to the UNS campus, namely Jebres, Pucangsawit and Mojosongo Villages, Jebres District, Surakarta City, Central Java, where the population sample of each village was taken intentionally (purposive sampling) as many as 15 people from each village, so there were as many as 15 people from each village. 45 respondents. From this research, it can be seen that the role of UPT Sebelas Maret University Library (UNS) Surakarta in empowering the literacy of the community around the campus is still quite low. It is proven by the data that only 35.6% of the total respondents have felt their role. The role of the UPT for the UNS library still needs to be improved so that it can touch the layers of society around the UNS campus. With a higher role for the community, it is hoped that it can foster interest and reading culture for the community. In addition, the community also hopes that the role of the UNS Library UPT can increase knowledge and community literacy.